Strengthening the role of State in School Education vis-à-vis the Private Initiative - Singh, PH. Newton (JOURNAL OF INDIAN EDUCATION, 2007)
The paper pleads for a strong and a more pro-active role of the State in view of the growth of the private schools especially in primary education sector. Most of the private schools, as many of the findings confirm, mostly cater education for the children of the wealthy families. In a developing country like India where illiteracy rate and also the never-enrolled rate is relatively high, giving a free hand to private players to deliver a primary public good like education will not portend well for the country. Moreover, fulfillment of the much desired objective of universal elementary education would remain a distant dream if the state withdraws itself from its responsibility and allows the government school system to deteriorate further till it dies a silent death.